(untitled) (Journal of humanities and social sciences exploratio, 2026)
In the current rapid development of mobile e-commerce, this article explores the marketing practice and development path of mobile e-commerce from six dimensions: convenience, security, diversity, innovation, autonomy, and interactivity. In response to issues such as user shopping experience, user information data security, and inaccurate customer marketing, this study proposes strategies including optimizing user shopping search recommendations, establishing a full process data security management system and monitoring system, selecting suitable e-commerce platform marketing models for customers, and promoting the sustainable development of mobile e-commerce. The aim of this study is to provide reference for the optimization and sustainable development of mobile e-commerce marketing.